2018
DOI: 10.1088/1681-7575/aaa16a
|View full text |Cite
|
Sign up to set email alerts
|

Development of large-area high-temperature fixed-point blackbodies for photometry and radiometry

Abstract: Large-area high-temperature fixed-point (HTFP) blackbodies with working temperatures of approximately 2748 K and 3021 K, based on an Re-C eutectic and a WC-C peritectic respectively, have been developed and investigated. The blackbodies have an emissivity of 0.9997, show high-quality phase-transition plateaus and have high repeatability of the melting temperatures, but demonstrate temperature differences (from 0.2 K to 0.6 K) compared with small-cell blackbodies of the same HTFP. We associate these temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Our assumption is supported by the experiment described in [19], showed that the difference approximately doubled with doubling the thickness of the cavity bottom, which confirms the temperature-drop effect but not emissivity effect.…”
Section: Large-area Wc-c Blackbody Temperature Measurementsupporting
confidence: 82%
See 3 more Smart Citations
“…Our assumption is supported by the experiment described in [19], showed that the difference approximately doubled with doubling the thickness of the cavity bottom, which confirms the temperature-drop effect but not emissivity effect.…”
Section: Large-area Wc-c Blackbody Temperature Measurementsupporting
confidence: 82%
“…The previous investigation showed that thermodynamic temperature of a large-cell fixed point blackbody is a bit lower than temperature of a small-cell one [19]. We suppose this difference is due to larger temperature drop across the back cavity wall because of larger radiation loss for the large cell (the phenomenon known as 'temperature drop effect').…”
Section: Large-area Wc-c Blackbody Temperature Measurementmentioning
confidence: 87%
See 2 more Smart Citations
“…The WC-C fixed-point has a temperature higher than that of any of the HTFPs covered in the CCT HTFP research plan, and the observed plateau has a better quality in terms of shape and repeatability [5][6][7]. Its temperature is comparable with that of quartz halogen lamps widely used in radiometry, and therefore WC-C is a very convenient reference source for spectral radiance and irradiance [8]. WC-C's long-term stability [9] allows checking for drift of optical sources and detectors.…”
Section: The Wc-c Peritectic Pointmentioning
confidence: 98%